2014
DOI: 10.1177/102490791402100304
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised, Cross over Study Using a Mannequin Model to Evaluate the Effects on CPR Quality of Real-Time Audio-Visual Feedback Provided by a Smartphone Application

Abstract: Objective:To evaluate the effect of real time feedback provided by smartphone application on cardiopulmonary resuscitation (CPR) performance. Methods: Participants were randomised in two groups based on whether chest compression with or without the assistance of the smartphone application. Both groups performed hands-only CPR on a mannequin for 4 minutes. Data on CPR performance of both groups was compared. To assess the reliability the feedback value, we compared the CPR data from Skillmeter and data from sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Recently, applications (apps) designed for smartphones with a built‐in accelerometer have been developed for CPR training with chest compression feedback . Several simulation studies have found that these can improve performance of chest compression and might therefore substitute for commercial feedback devices . These studies were conducted while the manikin was supine.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, applications (apps) designed for smartphones with a built‐in accelerometer have been developed for CPR training with chest compression feedback . Several simulation studies have found that these can improve performance of chest compression and might therefore substitute for commercial feedback devices . These studies were conducted while the manikin was supine.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous reporting prevented some meta-analyses. There were 23 directive feedback studies 50,[191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][212][213][214][215][216] showing that in comparison with no feedback devices, the use of feedback devices…”
Section: S256 Circulationmentioning
confidence: 99%
“…9,10,[15][16][17][18][19][20][21][22][23] Study characteristics Table 1shows the characteristics of the selected studies. The studies included five RCTs (45%), 9,16,19,22,23 five RCOTs (45%), 10,15,18,20,21 and an RT (9%). 17 Eight of 11 studies (73%) used smartphones 9,10,15-20 and 3 studies (27%) [21][22][23] used smartwatches for their CPR training intervention.…”
Section: Search Resultsmentioning
confidence: 99%
“…Five studies (45%) were rated as 'of some concern' or 'high' for this domain due to the lack of detailed information on the actual randomisation process used. 10,15,17,18,21 Second, 'bias due to deviation from intended intervention' was evaluated. Five RCTs/RTs (45%) were rated as 'of some concern' since they did not clearly comment on blinding to intervention.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation